Case report of a giant inguinal hernia causing intestinal obstruction - Sanjay, R.; Khan, Farukh; Gupta, Shalu; ., Prashant; ., Akash (International Surgery Journal, 2021)
Inguinal hernia is one of the ancient diseases that haunted the humanity from its very beginning to the modern times. Giant inguinal hernia is defined as an inguinal hernia that extends below the midpoint of inner thigh when the patient is in standing position. A 43 years old healthy male was affected by long standing, progressively enlarging right sided inguinal hernia for the past 21 years. His symptoms of abdominal discomfort and pain in lower abdomen after meal had worsened over time and he had lost 13 kg of weight in past 2 years. He had difficulty in micturition and gave history of constipation. Giant inguinal hernia is a type of hernia with massive contents inside the hernia sac and limited domain of abdominal cavity. The surgeon’s decision regarding the prevention of intra-abdominal hypertension is a crucial stage of overall management. Giant inguinal hernia is a very rare. It is defined as hernia sac extending below mid inner thigh in the standing position. Surgical repair is very challenging and has significant morbidity and mortality due to increased intra-abdominal pressure and abdominal compartment syndrome.